2016
DOI: 10.3847/0004-637x/824/1/5
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Abundances in NGC 5024 (M53): A Mostly First Generation Globular Cluster

Abstract: We present the Fe, Ca, Ti, Ni, Ba, Na, and O abundances for a sample of 53 red giant branch stars in the globular cluster (GC) NGC 5024 (M53). The abundances were measured from high signal-to-noise medium resolution spectra collected with the Hydra multi-object spectrograph on the Wisconsin–Indiana–Yale–NOAO 3.5 m telescope. M53 is of interest because previous studies based on the morphology of the cluster’s horizontal branch suggested that it might be composed primarily of first generation (FG) stars and diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
37
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 31 publications
(48 citation statements)
references
References 50 publications
8
37
2
1
Order By: Relevance
“…Our favourite option is the former, which is compatible with the large error bars of magnesium, relative to the overall Mg spread observed. This understanding is in agreement with the studies by Boberg et al (2016), who suggest that SG stars in M53 formed from gas diluted with pristine matter, and by Caloi & D'Antona (2011), that, based on the analysis of the HB, concluded that only a small helium spread, δY ∼ 0.04, is present, thus ruling out the existence of a purely AGB contaminated stellar component. Concerning the bottom-right panel of Fig.…”
Section: M53: a Cluster At The Edgesupporting
confidence: 91%
“…Our favourite option is the former, which is compatible with the large error bars of magnesium, relative to the overall Mg spread observed. This understanding is in agreement with the studies by Boberg et al (2016), who suggest that SG stars in M53 formed from gas diluted with pristine matter, and by Caloi & D'Antona (2011), that, based on the analysis of the HB, concluded that only a small helium spread, δY ∼ 0.04, is present, thus ruling out the existence of a purely AGB contaminated stellar component. Concerning the bottom-right panel of Fig.…”
Section: M53: a Cluster At The Edgesupporting
confidence: 91%
“…When compared to other methods of identifying multiple populations such as the Na-O anticorrelation (Carretta et al 2009a,b) and HST UV photometry (Milone et al 2017), we find that the CN band analysis classifies stars in common to these samples into the same populations. We do not find any of the outlying stars with enhanced CN and normal Na that have been discovered in M71, 47 Tuc, and M53 by Smith (2015a), Smith (2015b), and Boberg et al (2016a), respectively.…”
Section: Discussioncontrasting
confidence: 52%
“…Raising the separating value also brings the ratio of second generation stars from 60 % to 33 %, which comes closer to agreement with the ratio we find using δCN, the ratio found by Milone et al (2017) with HST photometry, and the ratio found by Bowman et al (2017) with narrow, CN-band photometry. Additionally with the exception of one HB star, we do not observe any CN-enhanced stars with normal [Na/Fe] values as reported by Smith et al (2013), Smith (2015a), and Boberg et al (2016) in M5, 47 Tuc, and M53, respectively.…”
Section: Discussionsupporting
confidence: 85%